2016
DOI: 10.1016/j.cmpb.2016.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Methods for generating paired competing risks data

Abstract: Background and objectives Clustered competing risks data arise often in genetic studies, multicenter investigations, and matched-pairs studies. In the last two decades, major advances in competing risks theory had been made. Many new statistical methods need to be evaluated via simulation studies. Some mechanisms for simulating clustered competing risks data have been considered in the literature. However, most of them produce data where the strength of the dependence between individuals within a cluster is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Assessment of the importance of communications with various groups of stakeholders (customers, employees, partners, governance agencies, the public) has shown that they are very not equivalent that in general is coordinated with the research conducted by Chernov D.V. [9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of the importance of communications with various groups of stakeholders (customers, employees, partners, governance agencies, the public) has shown that they are very not equivalent that in general is coordinated with the research conducted by Chernov D.V. [9].…”
Section: Resultsmentioning
confidence: 99%
“…With regard to the resource-providing communication capability, it is necessary to conduct a thorough audit of the company's policies, since communications in relation to them significantly determine both the level of information openness and the perception of the organization by stakeholders [9].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the foregoing, the following can be attributed to the principles of developing a competitive innovation project [2].…”
Section: Fig 1 Factors Of Competitiveness Of the Innovation Projectmentioning
confidence: 99%
“…Besides, it's important to intend that the division on the systematic and non-systematic risks is differ among different participants of the development process. For example, risks associated with the peculiarities of the real estate market are systematic for the developer, investor may consider them as non-systematic, because he has significantly wider selection box for the investment activity [4].…”
Section: Spbwosce-2016mentioning
confidence: 99%